Deradikalisasi dan Pembangunan Budaya Inklusif di Jawa Barat, Indonesia - Windy Dermawan; RMT Nurhasan Affandi; Gilang Nur Alam (Universitas Mathla'ul Anwar Banten, 2019)
RADICALIZATION AND THE DEVELOPMENT OF INCLUSIVE CULTURE IN WEST JAVA, INDONESIA. The aim of the Community Engagement (PPM) research is to explain efforts to deal with radicalization so that the country is not centric in the form of inclusive cultural development. The description seeks to trace the interpretation of Jatinangor District, Sumedang Regency, West Java Province. This was motivated by the tendency to strengthen radical understanding which was observed in West Java after the Reformation era in Indonesia. Strengthening radicalization can trigger the development of a culture of intolerance, verbal and physical violence, and exclusivism that is not impossible to bring the potential for national disintegration or threat to security in Indonesia. The study attachments in this PPM are Problem-Based Learning and Community-Based Research (CBR). Especially, in constructing ideas that are relevant to efforts so that problems in the community can be faced optimally. The formation of an inclusive culture is thought to enable the openness (inclusiveness) of society, tolerance, pluralism, collaboration and cooperation to control the diversity of identities in society. PPM is a follow-up from previous research which found that efforts to deal with radicalization were still state-centric. Based on the results of the PPM, it was concluded the need for awareness-raising and societal empowerment activities on an ongoing basis to deal with radicalization.